2002
DOI: 10.1016/s0001-2092(06)61065-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and its Chronic Complications

Abstract: Diabetes mellitus is a major cause of morbidity and mortality, and it is a major risk factor for early onset of coronary heart disease. Complications of diabetes are retinopathy, nephropathy, and peripheral neuropathy. Currently, treatment involves diet modification, weight reduction, exercise, oral medications, and insulin. In recent years, important advances have been made into the pathogenesis of diabetes that affect the cardiovascular, renal, and nervous systems; vision; and the lower extremities, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 42 publications
0
78
0
5
Order By: Relevance
“…The exposure of peripheral tissues and organs to hyperglycemia initiates enzymatic and non-enzymatic perturbations in cellular metabolism and in cell structure and function that lead to the development of diabetic complications, such as cardiovascular diseases, nephropathy, retinopathy or impaired wound healing (Aronson, 2008;Aronson and Rayfield, 2002;Bailes, 2002;Forbes and Cooper, 2013;Giacco and Brownlee, 2010;Nathan, 1993;Sayin et al, 2015). The observation of a variable propensity among type 1-and type 2 diabetic patients to develop such complications over the course of the disease have attracted attention and prompted genome-wide association studies in search for susceptibility and protective genes in vulnerable and unaffected diabetic patients (Lyssenko et al, 2008).…”
Section: Etiology and Progression Of T2dmmentioning
confidence: 99%
“…The exposure of peripheral tissues and organs to hyperglycemia initiates enzymatic and non-enzymatic perturbations in cellular metabolism and in cell structure and function that lead to the development of diabetic complications, such as cardiovascular diseases, nephropathy, retinopathy or impaired wound healing (Aronson, 2008;Aronson and Rayfield, 2002;Bailes, 2002;Forbes and Cooper, 2013;Giacco and Brownlee, 2010;Nathan, 1993;Sayin et al, 2015). The observation of a variable propensity among type 1-and type 2 diabetic patients to develop such complications over the course of the disease have attracted attention and prompted genome-wide association studies in search for susceptibility and protective genes in vulnerable and unaffected diabetic patients (Lyssenko et al, 2008).…”
Section: Etiology and Progression Of T2dmmentioning
confidence: 99%
“…Although daily glucose monitoring and exogenous insulin administration has been the standard therapy since the discovery of insulin, the poor control of blood glucose fluctuations with this therapy leads to many severe complications including neuropathy, nephropathy, retinopathy, heart disease, and atherosclerosis (Bailes, 2002;Bloomgarden, 2004;Hill, 2004). In 1993, the Diabetes Control and Complications Trial showed that strict control of blood glucose levels reduced the risk of developing diabetes-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…In type-2 diabetes, as in type 1 diabetes, there is often development of later complications in many tissues and organs due to metabolic and/or hormonal disturbances and microangiopathy. To date, at least 8 major complications have been found in both type-1 and type-2 diabetes, including retinopathy, nephropathy, cardiovascular disease, neuropathy, and wound healing problems (Bailes 2002).…”
mentioning
confidence: 99%